Validation of a Simple Isocratic HPLC Assay for the Detection of Oxytetracycline Residues in Chicken Meat - Lavanya, G; Ramesh, S; Ramasamy, T; Sangilimadan, K; Kalaiselvi, L (Indian Journal of Veterinary and Animal Sciences Research, 2025)
One of the major concerns in poultry rearing has been the use of antibacterials for the control of infections. The antibacterial drugs often find their way into the edible part of chicken, thus making it an issue of human food safety. Screening of chicken meat for antibacterials is thus an important part of ensuring food safety. Simple sensitive methods which could be adopted easily at laboratories of research institutes and testing centres are a need of the hour. In this study, one such assay method for the assay of oxytetracycline, a popularly used antibiotic in poultry farms, in broiler chicken meat standardized using High-performance liquid chromatography (HPLC) is described. The HPLC assay method consisted of a C18column as the stationary phase and a mobile phase consisting of 0.2M oxalic acid: Acetonitrile: Methanol (3.5:1:1, v/v) pumped in with the flow rate of 1.5 ml/ min and assayed at 360nm for detection of OTC The Limit of Detection and Limit of Quantification was 0.141 µg/ ml and 0.465 µg/ ml respectively. The total elution time was less than 4 minutes with a recovery rate of 105%. The results suggest that this method, with its high detection throughput and remarkable sensitivity and specificity, can be applied successfully for the field screening of oxytetracycline residue in chicken meat samples.